Implementation of the MMQ Agreement in KPR ProductsOn Increasing Financing at Bank Muamalat KCP Kuningan - Diah Syifaa'tu Zahro; Achmad Kholiq; Mariyah Ulfah (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2024)
In Indonesia, the housing problem is very big, especially in metropolitan areas. Bank Muamalat offers iB Hijrah KPR with Murabahah and musyarakah mutanaqishah contract options. The research was conducted to understand the implementation of the musyarakah mutanaqisah contract in KPR products. on KPR Financing at Bank Muamlat KCP Kuningan. And the results of implementing the musyarakah mutanaqisah agreement on KPR products in increasing KPR financing at Bank Muamalat KCP Kuningan. This research uses a qualitative approach, with data sources used namely primary and secondary, and data collection techniques of observation, interviews, and documentation. Bank Muamalat KCP Kuningan implements the musyarakah mutanaqisah agreement in the iB Hijrah KPR financing product through three stages, including BI Checking for husbands and wives with five columns of financial assessment. The financing process involves musyarakah mutanaqisah and ijarah contracts, where customers gradually buy a house from the bank. Despite facing challenges in public understanding and document requirements, the bank carried out a thorough feasibility assessment process. Thus, the implementation of the musyarakah mutanaqisah agreement was proven to have a positive impact on increasing mortgage financing. Increasing the number of customers and sales volume of mortgage products with promotional and educational efforts. Annual data records increases and decreases in mortgage financing at Bank Muamalat KCP Kuningan. As seen from the annual data of Bank Muamalat Indonesia for 2022-2023 there has been an increase and in 2019-2021 there has been an increase and decrease. Bank Muamalat KCP Kuningan succeeded in overcoming obstacles in understanding and obtaining IMB in the implementation of the Musyarakah Mutanaqisah KPR iB Hijrah Agreement by implementing a relief policy. As well as being able to restore increased financing using a promotion, and education to the community, educational institutions, and government.